PENERAPAN MODEL PROJECT BASED LEARNING PADA PEMBELAJARAN MENGONTRUKSI KARYA ILMIAH DI SMA - Nur Halimatusyadiyah Ms Lubis; Kamarudin; Hadiyanto (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
The project based learning model is a learningimodel that seeks to develop competence and learning skills through a series of activities to plan, implement and produce certain products which are contained in a container in the formiof a project. The objectivesito be achievediin this study are to describe the applicationiof the project basedilearning model to learning to construct scientific work in class XI IPA at SMA Negeri 9 Tanjung Jabung Barat. The approachiin this research is a qualitativeiapproach. The results of this study are that the application of PjBL can be used in learning to construct scientific work. This is evidenced by the value of students who are categorized as good. The PjBL learningimodel can increase motivationiand persistence in the learning process